Evaluasi Implementasi Model Keperawatan Berbasis Bukti dalam Meningkatkan Kualitas Asuhan Keperawatan di Rumah Sakit - Sudijanto, Dewi Astuti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Evidence-Based Nursing Practice (EBNP) is a nursing care approach that integrates current research evidence, clinical experience, and patient preferences to improve the quality of care. Its implementation in hospitals is believed to improve service quality and patient satisfaction, but still faces various challenges in the field. Objective: To evaluate the implementation of an evidence-based nursing model in improving the quality of nursing care in hospitals. Methods: This study used a descriptive evaluative design with a mixed methods approach. The sample consisted of 50 nurses and 100 inpatients at Hospital X, selected using purposive sampling. Instruments included a nurse knowledge and attitude questionnaire, a nursing practice observation checklist, a patient satisfaction questionnaire, and in-depth interviews. Quantitative data were analyzed using a paired t-test, while qualitative data were analyzed using thematic analysis. Results: The average nurse knowledge score increased from 65.4 to 84.6 (p < 0.001). Compliance with SOPs increased from 74% to 93%. Patient satisfaction increased from 78.2 to 90.1 (p < 0.001). Supporting factors for implementation included management support, training, and practice guidelines, while barriers included time constraints, high workload, and limited access to journals. Conclusion: EBNP implementation significantly improved knowledge, skills, procedural compliance, and patient satisfaction. It is recommended that hospitals provide ongoing training, facilitate access to scientific resources, and establish EBNP support teams.